Answer:
s = 19.1
Step-by-step explanation:
Simplifying
25.3 = s + 6.2
10011813 avatar
Solving
25.3 = 6.2 + s
Solving for variable 's'.
Move all terms containing s to the left, all other terms to the right.
Add '-1s' to each side of the equation.
25.3 + -1s = 6.2 + s + -1s
Combine like terms: s + -1s = 0
25.3 + -1s = 6.2 + 0
25.3 + -1s = 6.2
Add '-25.3' to each side of the equation.
25.3 + -25.3 + -1s = 6.2 + -25.3
Combine like terms: 25.3 + -25.3 = 0.0
0.0 + -1s = 6.2 + -25.3
-1s = 6.2 + -25.3
10011813 avatar
Combine like terms: 6.2 + -25.3 = -19.1
-1s = -19.1
Divide each side by '-1'.
s = 19.1
Simplifying
s = 19.1